Kryzys nieletniego i rodziny w kontekście umieszczenia w zakładzie poprawczym - Perska-Gradowska , Paulina (Studia Edukacyjne, 2022)
A juvenile’s punishable act may be perceived as a source of crisis and a consequence of remaining in a crisis, and the adjudication of a corrective measure against a minor and placement in a correctional facility is a critical life event, with consequences for both the minor and his family. The consequences include, for example, the disorganization of the current way of functioning of the family, a change in the educational environment, a sense of threat to the juvenile’s identity, and the loosening of family ties. From this perspective, an important task is to provide the juvenile and his family with appropriate support (institutional, information, psychological) to solve the crisis positively. One of the possibilities is to take action in the field of crisis intervention and specialist counseling. The crisis related to being placed in a correctional facility may be an opportunity for the juvenile and his family, especially in a situation where they want to receive help, and the functioning of the system and institutions will enable them to receive the necessary support.